2015
DOI: 10.2527/jas.2014-7953
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for yearling weight, carcass traits, and primal-cut yields of Hanwoo cattle1

Abstract: Genetic parameters associated with yearling weight, carcass traits, and primal-cut yields of male Hanwoo cattle were investigated using univariate and bivariate animal models. The mean yearling weight (YWT), carcass weight (CWT), longissimus muscle area (LMA), backfat thickness (BFT), and marbling score (MS) were 352.47 ± 0.40 kg, 337.39 ± 0.64 kg, 78.28 ± 0.13 cm2, 8.45 ± 0.05 mm, and 3.25 ± 0.03, respectively. Total primal-cut yield (TPC) was 78.95 ± 0.10% of CWT, of which 42.3% was contributed by the forequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(86 citation statements)
references
References 62 publications
43
41
0
1
Order By: Relevance
“…The CWT found in this study was in line with Moon et al [15] and Baik et al [16]. The averages of different loin cuts (tenderloin: 1.63%, striploin: 9.95%, and sirloin: 1.99%) reported by Choi et al [9] was somewhat lower than the present study. They also reported a total primal-cut average of 78.95%, which coincided greatly with RCR in this study.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The CWT found in this study was in line with Moon et al [15] and Baik et al [16]. The averages of different loin cuts (tenderloin: 1.63%, striploin: 9.95%, and sirloin: 1.99%) reported by Choi et al [9] was somewhat lower than the present study. They also reported a total primal-cut average of 78.95%, which coincided greatly with RCR in this study.…”
Section: Resultssupporting
confidence: 91%
“…The LMR tended to be somewhat more heritable with model 2 (0.42) than with model 1 (0.36). Earlier Choi et al [9] in Hanwoo males showed h 2 for particular loin cuts (tenderloin: 0.41; sirloin: 0.60; striploin: 0.64) instead of our estimate for overall LMR (0.36) which found to be seemingly in an overall agreement with the present estimate. Similar overall agreeable ranges for heritability were observed with Pabiou et al [21], which also estimated h 2 for sirloin, tenderloin, striploin and percentage of retail product.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations